PENGEMBANGAN BUKU AJAR BAHASA PRANCIS TINGKAT A1 BIDANG RESTORAN DAN DAPUR DI POLTEKPAR LOMBOK - Rizda Endean Ngoluanta Batubara (LPSDI Bina Patria, 2024)
Language is a verbal communication tool used by humans to convey ideas and desires. There are four language skills, they are (1) listening, (2) speaking, (3) reading, and (4) writing. French terminology is widely used in tourism and hospitality, especially in the areas of restaurants and kitchens. Examples: à la carte (single menu), gueridon service (chef serving guests cooking in front of guests using a pushcart), banquet, croissant (typical French bread shaped like a crescent moon), baguette (typical French bread shaped like a stick), chef (head cook), and so on. Until this date, France is the ancestor and is famous for its culinary centres and restaurants. A significant problem that needs to be addressed regarding French learning at Politeknik Pariwisata Lombok is the unavailability of A1 level French textbooks on restaurant and kitchen. The French books that are available are general French, while a French textbook specifically for restaurants and kitchens is highly needed. The methodology used in this study is Research and Development (R&D). In the 2022 research, the author has conducted research on analyzing the need for textbooks to be developed. The author analyzed the needs by interviewing four sources, including: students at the Politeknik Pariwisata Lombok, Food and Culinary Arts study program, French lecturers at Universitas Negeri Medan and at Perguruan Tinggi Negeri Pariwisata (PTNP) of the Ministry of Tourism and Creative Economy/Barekraf, and hotel industry based adjunct lecturers at Politeknik Pariwisata Lombok. The author's 2023 research focuses on developing A1 level French textbooks based on the need analysis from the four sources. The data obtained from developing textbooks is in the form of material that can be directly applied in restaurants and in the Politeknik Pariwisata Lombok practical kitchen. The textbook contains simple conversations supported by colorful pictures, YouTube links to watch videos or audio, and four basic language skills and vocabulary practice. The textbook has also been assessed by expert validators from lecturers who teach French in hotels and restaurants. The conclusion of the research and development of A1 level French textbooks on restaurant and kitchen at Politeknik Pariwisata Lombok is that the textbook can be used in two study programs, namely the Food Management and Culinary Arts study programs at Politeknik Pariwisata Lombok